2003
DOI: 10.1007/s00384-003-0483-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electrical stimulation in constipated patients with impaired rectal sensation

Abstract: Our findings show that the efficacy of EST can be comparable to BFT in a subgroup of constipated patients, especially those with impaired rectal sensation. EST might be considered as an adjunctive therapeutic modality for the management of functional constipation with impaired rectal sensation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 19 publications
1
55
0
1
Order By: Relevance
“…The patient felt that her quality of life had improved stating that "improved self confidence means I can be my own advocate rather than feeling vulnerable or passive". These results are similar to those reported after implantation of anterior sacral root stimulators [4][5][6][7][8].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The patient felt that her quality of life had improved stating that "improved self confidence means I can be my own advocate rather than feeling vulnerable or passive". These results are similar to those reported after implantation of anterior sacral root stimulators [4][5][6][7][8].…”
Section: Discussionsupporting
confidence: 81%
“…Severe cases may require surgical treatment, such as subtotal colectomy and ileorectal anatomisis. In recent years sacral nerve stimulation has been shown to reduce constipation in patients with diminished rectal sensation, slow colonic transit time and reduced urge to defecate [4][5][6][7]. However, the implantation of the stimulator is an invasive surgical procedure that is associated with potentially serious complications such as infection, cerebrospinal fluid collection around the receiver and receiver failure [8].…”
Section: Introductionmentioning
confidence: 99%
“…[205][206][207] Acknowledgements: We would like to express our sincere gratitude to Eun-Ae Jeong, PhD of the Library of Medicine of Soonchunhyang University who searched existing guidelines during the first phase of the systematic literature review. In addition, we would like to thank Prof. Seung-Jae Myung (Department of Gastroenterology, Asan Medical Center, University of Ulsan College Medicine) who reviewed the draft of this manuscript in the peer review process.…”
Section: Electrical Stimulation Therapymentioning
confidence: 99%
“…3,4 Just like the complexity in the definition of the functional and secondary constipation, the management pathway is also understandably difficult and challenging for both gastrointestinal physicians and gastrointestinal surgeons. Majority of the constipation experts offers several interventions to manage chronic constipation, with initial advice of life style change and failure to [16][17][18][19] Among novel pharmacological agents, cisapride, a pro-motility medicine, which acts as gut prokinetic therapy, was used clinically for the treatment of chronic constipation and studies reported cisapride effectively reduced the need for first and second line laxatives with optimized stool consistency, but failed to demonstrate effect on gut peristalsis in patients with chronic idiopathic constipation. 20 Tegaserod, a selective 5-hydroxytryptamine 4 (5-HT 4 ) receptor agonist, is reported to be a more successful novel pharmacotherapy agent than placebo in providing relief from the symptoms of chronic constipation, including increased bowel-movement frequency, decreased straining, or hard or lumpy stool in addition to reduced abdominal discomfort/pain, and bloating/distension.…”
Section: Introductionmentioning
confidence: 99%